FAKTOR STRATEGI PEMBELAJARAN AKHLAK DI TK TARBIAYATUL FURQAN KECAMATAN KANDANGAN - Salhah Salhah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This research departs from the importance of a strategy used by the teacher in the teaching and learning process so that it can influence students to achieve learning objectives effectively and efficiently in creating expected learning situations and forming character and educating students to become faithful, noble, wholehearted, knowledgeable, capable, creative, independent, and become some religious children. This study aims to find out how the strategy of teaching morals is in the Kindergarten of Tardayatul Furqan, Kandangan District and what factors influence it. This research is a field research (field research). Influencing factors that influence moral learning strategies in Tarbiatul Furqan Kindergarten, Kandangan District, in terms of teacher factors, namely experience, level of education, supporting facilities, in terms of student factors, namely attention and interest in learning.